Renewable Energy and Sustainable Technologies for Building and Environmental Applications Options for a Greener Future - Ahmad, Mardiana Idayu; Ismail, Mazran; Riffat, Saffa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This diverse resource on renewable energy and sustainable technologies highlights the status, state of the art, challenges, advancements and options in areas such as energy recovery systems, turbine ventilators, green composites, biofuels and bio-resources for energy production, wind energy, integrated energy-efficient systems, thermal energy storage, natural ventilation & day-lighting systems, and low carbon technologies for building and environmental applications. It is designed to serve as a reference book for students, researchers, manufacturers and professionals working in these fields. The editors have gathered articles from world-leading experts that clearly illustrate key areas in renewable energy and sustainability. The distinct role of these technologies in future endeavors is stressed by taking into account the opportunities to contribute with new approaches, methods and directions for building and environmental applications. The in-depth discussion presented in this book will give readers a clear understanding of every important aspect of each technology$1 (Bs applications, optimum configuration, modifications, limitations and their possible improvements.s
Inverse Problem for Phase Change Materials and Preparation in Building Envelope -- Natural Composite Membranes for Water Remediation: Towards A Sustainable Tomorrow -- Polymeric Heat Exchangers: Effect of Chemistry and Chemical Composition to Their Performance -- Solar Induced Ventilation Strategies in Contemporary Tropical Buildings: A Review -- Insights to Current Lighting Technologies and Low Environmental Impact Artificial Lighting -- Applications of Air-to-Air Energy Recovery System in Various Climatic Conditions: Towards Reducing Energy Consumption in Buildings -- Toplighting Systems for Improving Indoor Environment: A Review -- Polychaetes as Ecosystem Engineers: Agents of Sustainable Technologies -- The Cooling Effects of Plants on the Built Environment -- Turbine Ventilator as Low Carbon Technology -- Green Binderless Board from Oil Palm Biomass -- Life Cycle Analysis of Building Materials -- A Review on Biofuel and Bio-Resources for Environmental Applications -- Energy Recovery by Biological Process.
Keywords: Energy; Renewable energy resources; Renewable energy sources; Alternate energy sources; Green energy industries; Sustainable development; Energy; Renewable and Green Energy; Renewable and Green Energy; Sustainable Development; Electronic books